2016
DOI: 10.4103/0973-029x.180922
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical expression of p53 and its clinicopathological correlation with modified Anneroth′s histological grading system

Abstract: Introduction and Objectives:Oral squamous cell carcinoma (OSCC) is an epithelial neoplasm generally beginning as focal overgrowth of altered stem cells near the basement membrane, moving upward and laterally, replacing the normal epithelium. Histopathological grading has been used for many decades in an attempt to predict the clinical behavior of oral squamous cell carcinoma. In the present study, Forty biopsies were studied for histological grading and p53 expression. The p53 expression was studied in relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
(32 reference statements)
1
5
0
Order By: Relevance
“…Therefore, it seems reasonable to assume that high p53 protein expression levels detected by IHC reflect the extended half-life of p53 protein encoded by TP53 gene mutation (3). Similarly to published studies (3,14,15) we found correlation between p53 overexpression and grade of OSCC. The authors postulated that patients with OSCC whose tumor showed high expression of p53 protein had worse clinicopathological parameters and presented aggressive behavior (3,14).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Therefore, it seems reasonable to assume that high p53 protein expression levels detected by IHC reflect the extended half-life of p53 protein encoded by TP53 gene mutation (3). Similarly to published studies (3,14,15) we found correlation between p53 overexpression and grade of OSCC. The authors postulated that patients with OSCC whose tumor showed high expression of p53 protein had worse clinicopathological parameters and presented aggressive behavior (3,14).…”
Section: Discussionsupporting
confidence: 86%
“…The loss of p53 function with resultant overexpression has been reported in various human tumors such a breast, brain, rectum, colon, oesophagus, lung cancers and OSCCs (4). Previous studies have shown that oral carcinomas with overexpression/mutation of p53 grow faster and have aggressive nature and poor prognosis (1,3,15).…”
mentioning
confidence: 99%
“…Previous literature also showed association of p53 expression with tumor grade and other histologic features. Dave et al in a study involving 40 cases of HNCC found a significant association of p53 expression with tumor grade and other histologic parameters like degree of keratinization [ 11 ]. Although we found significant association of p53 expression with tumor grade, however association with other histologic parameters was not noted.…”
Section: Discussionmentioning
confidence: 99%
“…P53 in proven to be involved in apoptosis and cell-cycle control making it a plausible biomarker of malignant potential. [ 8 9 10 ] Ki-67 can be detected in phases G1, S, G2 and M of the cell cycle, but not on G0 phase, exclusively in the nuclei of cycling cells making it a reliable marker of proliferating cells. [ 2 ]…”
Section: Discussionmentioning
confidence: 99%
“…in which 65% expression of p53 was found. [ 9 ] Their study showed significant correlation of grading parameters like the degree of keratinization, nuclear pleomorphism, number of mitosis and lymphoproliferative infiltrate with p53 expression. The increasing P53 expression along the increasing grade of tumor severity is proven in many studies.…”
Section: Discussionmentioning
confidence: 99%